The Lived Experiences of the Lombok Earthquake Survivors - Tauba, Ahmad Mumtaz; Suryani, Suryani; Rafiyah, Imas (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: The large-scale earthquake which had struck off Lombok, an island in West Nusa Tenggara, made the survivors faced poor conditions, difficulties, and lack of supplies. Besides physical losses, the survivors also experienced various psychological health disorders that significantly affected their psychological condition as well as life.Purpose: This study was aimed at exploring and gaining deeper meaning from the lived experiences of the Lombok earthquake survivors.Methods: This study used a qualitative method with a descriptive phenomenological approach to elucidate the phenomena from experiences. The participants were ten (10) survivors of the Lombok earthquake, who were determined by purposive sampling. Data were collected through in-depth interviews and analyzed using Colaizzi's method.Results: The results showed six emerging themes, including (1) problems solving skills when disaster strikes, (2) surviving from the limitations and difficulties, (3) feeling accustomed to earthquake, (4) family is a key source of strength to continue life, (5) getting closer to God by doing religious prayers and actions to have peace of mind, and (6) learning from the disasters to become a better human being.Conclusion: The lived experience of the Lombok earthquake survivors was a long journey where they survived and adapted the difficult situations, as later, they could turn the under-pressure conditions to chances for their personal development. The findings of this study provide insights for nurses to greatly contribute to solving post-disaster psychological issues by strengthening the survivors’ religious aspects, trauma healing, play therapy, and peer-support group.